The Formation of a Post-Peronist Generation: Intellectuals and Politics in Argentina through the Lens of Contorno (1953-1959) - Carassai, Sebastián Pablo (2010)
A significant segment of the Argentine intelligentsia experienced the Revolution of September 1955, which overthrew General Juan Domingo Perón, as a moment of liberation. With some exceptions, such as Arturo Jauretche and Raúl Scalabrini Ortiz among others, the cultural politics of Peronism had not managed to gain many followers in the course of its ten-year experiment. During the two consecutive Perón governments (1946-1955) the often implicit, and occasionally explicit, opposition between intellectuals and Peronism only intensified. I contend that an analysis of this opposition is indispensable for understanding the redrawing of crucial definitions within the intellectual field at that time. Due to its profound social and cultural impact, the experience of Peronism compelled Argentine intellectuals, whether or not it was their original intention, to enter the political arena, not so much because their interests shifted from culture to politics, but rather because they came to conceive the cultural world as political.